Evolution and mechanism of the trade network of global aluminum resource - Guimei, ZHAO; Xianxiang, WANG; Yong, GENG (Zi yuan ke xue, 2025)
[Objective] Investigating the evolution and mechanism of the global aluminum resource trade network contributes to a deeper understanding of the evolution process and underlying logic of the global aluminum trade pattern, which is of great significance for ensuring the security of aluminum resource supply. [Methods] Using the complex network analysis method, this study constructed a global aluminum resource trade network to characterize its trade patterns and spatiotemporal characteristics from 2011 to 2020. An exponential random graph model (ERGM) was then employed to reveal the evolution mechanism of the global aluminum resource trade network, aiming to provide decision-making references for ensuring the sustainable supply of aluminum resources in China. [Results] (1) The scale of global aluminum resource trade experienced constant fluctuations, and the trade relationships between countries (regions) gradually strengthened. However, only a few countries (regions) in the global aluminum resource trade network possessed the majority of trading partners. Germany, India, and the United States occupied central positions in the global aluminum trade network, while the centrality of the Netherlands, China, and Turkey increased significantly. These countries had strong influence on the aluminum resource trade network. (2) The global aluminum resource trade exhibited distinct reciprocity, and the interaction of endogenous and exogenous factors jointly promoted the dynamic evolution of the global aluminum resource trade network. Meanwhile, aluminum resource trade remained inactive between countries with similar levels of economic development, and countries with low per capita income showed a stronger willingness to export aluminum. Trade protection policies hindered the flow of global aluminum resources. In addition, language differences were not the main barrier to aluminum resource trade between countries, while geographical distance and proximity significantly affected the evolution of the global aluminum resource trade network. [Conclusion] Based on a clear understanding of the characteristics and evolution mechanism of the global aluminum resource trade network, China should fully leverage its core position and bridging role in the aluminum resource trade network, coordinate both domestic and international markets and implement targeted trade strategies to ensure the security and stability of China’s aluminum resource supply.